Conceptual framework for precision cancer medicine in Germany: consensus statement of the Deutsche Krebshilfe working group ‘Molecular Diagnostics and Therapy’" - Westphalen, Christoph Benedikt; Bokemeyer, Carsten; Büttner, Reinhard; Fröhling, Stefan; Gaidzik, Verena I.; Glimm, Hanno; Hacker, Ulrich T.; Heinemann, Volker; Illert, Anna L.; Keilholz, Ulrich; Kindler, Thomas; Kirschner, Martin; et al. (European journal of cancer, 2020)
Precision cancer medicine (PCM) holds great promises to offer more effective therapies to patients based on molecular profiling of their individual tumours. Although the PCM approach seems intuitive, multiple conceptional and structural challenges interfere with the broad implementation of PCM into clinical practice. Accordingly, concerted national and international efforts are needed to guide the further development and broad adoption of PCM in Germany. With support of the ‘German Cancer Aid’ (Deutsche Krebshilfe [DKH]) a task force ‘Molecular Diagnostics and Therapy’ was implemented. In two workshops supported by the DKH, delegates from the fourteen comprehensive cancer centresidentified key topics essential to implement quality-guided, harmonized and adaptable PCM. Based on an online questionnaire and using a modified Delphi approach, nine statements were drafted and evaluated within the group. These statements could serve as a basis to define a collaborative strategy for PCM in the future with the aim to sustain and further improve its quality.
Working Group Molecular Diagnostics and Therapy: Ralf Bargou (Würzburg), Hendrik Bläker (Leipzig), Melanie Börries (Freiburg), Christian Brandts (Frankfurt), Melanie Demes (Frankfurt), Alexander Desuki (Mainz), Hartmut Döhner (Ulm), Justus Duyster (Freiburg), Nadine Gaisa (Aachen), Annkristin Heine (Bonn), Christoph Heining (Dresden), Peter Horak (Heidelberg), Ivan Jelas (Berlin), Philipp J. Jost (München), Andreas Jung (München), Thomas Kirchner (München), Frederick Klauschen (Berlin), Simon Kreutzfeldt (Heidelberg), Jörg Kumbrink (München), Volker Kunzmann (Würzburg), Silke Lassmann (Freiburg), Klaus Metzeler (München), Peter Möller (Ulm), Nadina Ortiz-Brüchle (Aachen), Claudia Paret (Mainz), Natalie Pelusi (Bonn), Christoph Peters (Freiburg), Nicole Pfarr (München), Daniela Richter (Dresden), Kristina Riedmann (München), Damian Rieke (Berlin), Christoph Ritzel (Mainz), Dirk Schadendorf (Essen), Hans-Ulrich Schildhaus (Essen), Hubert Schorle (Bonn), Thomas Seufferlein (Ulm), Ronald Simon (Hamburg), Albrecht Stenzinger (Heidelberg), Ghazaleh Tabatabai (Tübingen), Janna-Lisa Velthaus (Hamburg), Martin Werner (Freiburg), Peter J. Wild (Frankfurt), Jürgen Wolf (Köln)
Gesehen am 08.09.2020